Method of Determining the Beginning of the Lunar Month (Scientific Study of the Syattariyah and Naqsyabandiyah Orders in Indonesia) - Riza Afrian Mustaqim (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2023)
The problem of very significant differences is present in the determination of the beginning of the Kamariah month of the Shattariyah and Naqsyabandiyah communities in Indonesia. The difference is motivated by the use of conventional methods in determining the beginning of the Kamariah (Lunar) month. This research explores how the method of determining the beginning of the Kamariah month of the Shattariyah and Naqsyabandiyah congregations. how is the scientific verification of the method of determining the beginning of the Kamariah month of the Shattariyah and Naqsyabandiyah congregations. This research is a scientific research. The analysis used in this research is component analysis. The results of this research show that First, the method of determining the beginning of the Kamariah month applied by these two communities, the Shattariyah and Naqsyabandiyah communities, is a conventional method, especially in the hisab that is applied. In addition, there is Rukyatul Hilal, which is also classified as conventional in its application. Secondly, the method of determining the beginning of the month of Kamariah in the Shattariyah and Naqsyabandiyah orders cannot be scientifically proven in the Scientific Review. There are many errors in determining the beginning of the Kamariah month according to this order. The irrelevant Hisab method is the main cause. On the other hand, Rukyatul Hilal, which is considered as a determinant, has shortcomings in its application so that it is not able to detect the presence of Hilal accurately and precisely.